The Production of Pyocins of Pseudomonas aeruginosa: A Structure and Methodology Review: Pyocins Production: A review Study - Al-Mizel, Ali; Ajah, Hamzia Ali; Abudlrazaq, Raghad Abdullatif (ASJ - Academic Science Journal, 2025)
The main objective of this review is to clarify the definition, types and structures of pyocins. It also highlights the various methods and their procedures that have been employed to screen, extract, isolate and purify pyocins from Pseudomonas aeruginosa. Furthermore, this study provides an analysis of the advantages and disadvantages associated with each approach. This may aid future research in combating antibiotic resistance that has become increasingly prevalent in recent years creating a burden on both the medical and financial fronts. In recent years, the resistance to antibiotics has increased rapidly due to the misuse and the presence of inhibitory and sub-inhibitory concentrations of antibiotics in various terrestrial and aquatic environments. The misuse of these antibiotics has led to the emergence and spread of antibiotic resistant microbes, posing challenges in treating common infections. The understanding of these findings is crucial for devising strategies to explore alternatives such as pyocins to replace conventional antibiotics capable of efficiently combating bacterial illnesses. The study concluded that some techniques may not be very effective at differentiating between types of pyocins though they are cheap which makes them beneficial for screening. On the other hand other techniques accurately identify the pyocins, nevertheless, they are costly, complicated, and need specific tools though some are more expensive than others. Some techniques lack specificity, and left out centrifuge specifics that are essential to maintaining consistency between experiments. The initial ammonium sulphate saturation has not been mentioned and a range with ammonium sulphate precipitation with the highest yield should be measured. Numerous strains of indicators have been employed, indicating the necessity for more extensive research to identify trustworthy indicators for consistent outcomes.